EVOLVING PARADIGMS IN POSTOPERATIVE PAIN MANAGEMENT: COMPARATIVE EFFICACY AND SAFETY OF CONCENTRATED INTRAVENOUS PARACETAMOL BOLUS VERSUS CONVENTIONAL DILUTED FORMULATIONS - Dr Sucheta Meshram (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Intravenous (IV) paracetamol is a cornerstone of multimodal analgesia, providing opioid-sparing effects and a favorable safety profile in postoperative patients. The conventional 1% w/v formulation (100 ml) requires slow infusion, whereas concentrated preparations (1000 mg/4 ml) offer potential logistical advantages via bolus administration. Objective: To comprehensively review the pharmacological basis, clinical evidence, and safety profiles of IV paracetamol in postoperative pain, with a focus on emerging concentrated formulations. Methods: A comprehensive literature search was conducted in PubMed, Scopus, and Embase databases from 2000 to 2024, analyzing randomized controlled trials (RCTs), meta-analyses, and pharmacokinetic studies comparing various IV paracetamol formulations in surgical populations. Findings: IV paracetamol reduces postoperative pain scores and opioid requirements across diverse surgeries. While conventional infusions have proven safety and efficacy, emerging concentrated formulations require robust clinical validation for pharmacokinetic equivalence, local tolerability, and hemodynamic safety. Conclusion: Concentrated paracetamol bolus injections may simplify administration without compromising analgesic efficacy, pending confirmatory evidence from large multicentric trials.